Analysis of Crater Development Around Damaged Pipelines Using the Material Point Method. (2017) - Martinelli, Mario; Tehrani, Faraz S.; Galavi, Vahid
Abstract: In this study, the material point method (MPM) is used to simulate and analyze crater development around a pipeline embedded in sand. To that end, a double-point MPM formulation in conjunction with an elastic-perfectly plastic soil model with Mohr-Coulomb failure criterion is used to simulate the onset and evolution of crater in fully saturated sands. The onset of failure is also simulated with standard finite element method. The results show that the double-point MPM formulation can satisfactorily capture the essential features of the crater development.